2017
DOI: 10.1002/jcp.25823
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, biophysical, and pharmacological properties of calcium‐activated chloride channels

Abstract: Calcium-activated chloride channels (CaCCs) are a family of anionic transmembrane ion channels. They are mainly responsible for the movement of Cl and other anions across the biological membranes, and they are widely expressed in different tissues. Since the Cl flow into or out of the cell plays a crucial role in hyperpolarizing or depolarizing the cells, respectively, the impact of intracellular Ca concentration on these channels is attracting a lot of attentions. After summarizing the molecular, biophysical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 155 publications
0
15
0
2
Order By: Relevance
“…Clearly, a deep understanding of the mechanisms involved in protein and gene regulation by Cl − is important to understand better the pathologies associated with different Cl − channels (channelopathies) (Statland, Phillips & Trivedi, 2014;Suetterlin, Mannikko & Hanna, 2014;Poroca, Pelis Menegazzi et al (2000) & Chappe, 2017). The role of Cl − channels in disease has been extensively reviewed elsewhere (Kunzelmann & Mall, 2002;Pedemonte & Galietta, 2014;Hoffmann et al, 2015;Abeyrathne, Chami & Stahlberg, 2016;Ito, 2016;Whitlock & Hartzell, 2016;Poroca et al, 2017;Kamaleddin, 2018). The early history of the role of Cl − in muscle was recently reviewed by Hutter (2017).…”
Section: CL − Effects In Eukaryotic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, a deep understanding of the mechanisms involved in protein and gene regulation by Cl − is important to understand better the pathologies associated with different Cl − channels (channelopathies) (Statland, Phillips & Trivedi, 2014;Suetterlin, Mannikko & Hanna, 2014;Poroca, Pelis Menegazzi et al (2000) & Chappe, 2017). The role of Cl − channels in disease has been extensively reviewed elsewhere (Kunzelmann & Mall, 2002;Pedemonte & Galietta, 2014;Hoffmann et al, 2015;Abeyrathne, Chami & Stahlberg, 2016;Ito, 2016;Whitlock & Hartzell, 2016;Poroca et al, 2017;Kamaleddin, 2018). The early history of the role of Cl − in muscle was recently reviewed by Hutter (2017).…”
Section: CL − Effects In Eukaryotic Cellsmentioning
confidence: 99%
“…We have recently identified additional steps in CFTR signalling mechanisms that involve Cl − (Valdivieso et al, 2016, IL-1β Massip-Copiz et al, 2017, 2018 and c-Src , 2018, which may explain the reduced mitochondrial Complex I activity (Valdivieso, 2009;Valdivieso et al, 2012;Clauzure et al, 2014) and increased ROS levels found in cultured CF cells (Clauzure et al, 2014. Cl − modulates IL-1β mRNA and protein expression in a biphasic way, with maximal expression at 75 mM [Cl − ] i in the presence of nigericin and tributyltin .…”
Section: CL − As a Signalling Effector For Cftrmentioning
confidence: 99%
“…TMEM16A is expressed in ICCs, various epithelial cells (airway, salivary gland, stomach, and pancreas), the urogenital tract, and vascular smooth muscle. Modulation of TMEM16A activity has been proposed for various indications including gut dysmotility, inflammatory airway disorders, hypertension, and some cancers (18). Here, we found that pharmacological inhibition of TMEM16A in mice delayed gastric emptying and improved oral glucose tolerance without impairing intestinal transit.…”
Section: Discussionmentioning
confidence: 68%
“…CaCCs are widely expressed in many cell types, where they are involved in epithelial fluid secretion, cell proliferation, neuronal excitability, and signal transduction (18). TMEM16B, the closest homolog of TMEM16A in the TMEM16 protein family, also functions as a CaCC, though mainly in olfactory and retinal signal transduction (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…ICl‐G2, on the other hand, is a type of chloride current that depends of intracellular calcium (ICl,Ca) because, as we showed, ICl‐G2 currents were abolished after chelating the intracellular content of free calcium, by injection of BAPTA into oocytes previously injected with mRNA of Giardia , however ICl‐G2 currents are restituted after incubation with ionomycin, which premeabilizes the plasma membrane, and addition of calcium to the bathing media. Besides its dependence of intracellular calcium, the permeability sequence of ICl‐G2 (SCN − >I − >Br − >Cl − >F − >MS − ) compares to that of CaCC channels: SCN − > I − > NO 3 − > Br − > Cl − > F − (Kamaleddin ). The pharmacological profile is also similar; As shown above, ICl‐G2 are blocked by NPPB, DIDS, SITS, 9AC, and DPC, whereas CaCC are described to be blocked by niflumic acid, NPPB, 9AC, and DIDS.…”
Section: Discussionmentioning
confidence: 99%